2021
DOI: 10.1182/bloodadvances.2020002819
|View full text |Cite|
|
Sign up to set email alerts
|

KDM5A suppresses PML-RARα target gene expression and APL differentiation through repressing H3K4me2

Abstract: Epigenetic abnormalities are frequently involved in the initiation and progression of cancers, including acute myeloid leukemia (AML). A subtype of AML, acute promyelocytic leukemia (APL), is mainly driven by a specific oncogenic fusion event of promyelocytic leukemia–RA receptor fusion oncoprotein (PML-RARα). PML-RARα was reported as a transcription repressor through the interaction with nuclear receptor corepressor and histone deacetylase complexes leading to the mis-suppression of its target genes and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“… 429 Likewise in leukemia, CPI-455 treatment sensitized acute promyelocytic leukemia (APL) cells to all-trans retinoic acid-induced differentiation. 430 Importantly, CPI-455 may also be applied in the context of inflammatory diseases. Dexmedetomidine (DEX) is frequently used to prevent excessive inflammatory response in sepsis-induced organ failure.…”
Section: Jmjd Proteins As Therapeutic Targetsmentioning
confidence: 99%
“… 429 Likewise in leukemia, CPI-455 treatment sensitized acute promyelocytic leukemia (APL) cells to all-trans retinoic acid-induced differentiation. 430 Importantly, CPI-455 may also be applied in the context of inflammatory diseases. Dexmedetomidine (DEX) is frequently used to prevent excessive inflammatory response in sepsis-induced organ failure.…”
Section: Jmjd Proteins As Therapeutic Targetsmentioning
confidence: 99%
“…Chandra et al showed that NUP98 fusion proteins, including NUP98-KDM5A, form leukemia-related nuclear condensates, thus leading to leukemogenesis [85]. In addition to NUP98-KDM5A fusion, KDM5A has been shown to be involved in the progression of acute promyelocytic leukemia (APL) [86]. KDM5A contributes to the inhibition of differentiation in APL cells by repressing PML-RARα target genes via demethylating H3K4me2 [86].…”
Section: Kdm5amentioning
confidence: 99%
“…In addition to NUP98-KDM5A fusion, KDM5A has been shown to be involved in the progression of acute promyelocytic leukemia (APL) [86]. KDM5A contributes to the inhibition of differentiation in APL cells by repressing PML-RARα target genes via demethylating H3K4me2 [86].…”
Section: Kdm5amentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these leukemic cell lines hold the capacity to potentially differentiate into different hematopoietic lineages upon treatment with inducers. For example, the THP1 and U937 cell lines can be efficiently differentiated into macrophages using phorbol 12-myristate 13-acetate (PMA), and NB4 cells can be differentiated into granulocytes using all-trans retinoic acid (ATRA) or dimethyl sulfoxide (DMSO) ( Mendoza-Coronel and Castanon-Arreola, 2016 ; Xu et al, 2021 ). However, factors such as the culture media formulations, cell density, serum, and lack of homogeneous protocols affect the gene expression profile of cell lines.…”
Section: Introductionmentioning
confidence: 99%